2021
DOI: 10.1097/lgt.0000000000000593
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Unmet Basic Needs to Improve Colposcopy Adherence Among Women With Abnormal Cervical Cancer Screening

Abstract: Objectives The aims of the study were to identify unmet basic needs (BNs) among women referred to colposcopy, to assess patient acceptability/satisfaction with assistance from a navigator to address unmet BNs, and to estimate adherence to colposcopy. Methods Women were recruited between September 2017 and January 2019 from 2 academic colposcopy centers, one serving a rural and one an urban area. Basic needs were assessed by phone before colposcopy appoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Many of the studies focused on the follow-up of women in low-resource populations/settings. Of the 28 studies included for data extraction, 10 focused on interventions directed towards low-income populations [ 20 , 22 , 23 , 26 , 31 , 34 , 35 , 38 , 42 , 46 ], five addressed follow-up for racial minorities [ 21 , 24 , 30 , 40 , 43 ], one focused on addressing follow-up of women older than 65 years of age [ 33 ] and three served a combination of minority and low-income populations [ 28 , 32 , 39 ]. Nine of the studies did not describe a specific patient population group [ 19 , 25 , 27 , 29 , 36 , 37 , 41 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the studies focused on the follow-up of women in low-resource populations/settings. Of the 28 studies included for data extraction, 10 focused on interventions directed towards low-income populations [ 20 , 22 , 23 , 26 , 31 , 34 , 35 , 38 , 42 , 46 ], five addressed follow-up for racial minorities [ 21 , 24 , 30 , 40 , 43 ], one focused on addressing follow-up of women older than 65 years of age [ 33 ] and three served a combination of minority and low-income populations [ 28 , 32 , 39 ]. Nine of the studies did not describe a specific patient population group [ 19 , 25 , 27 , 29 , 36 , 37 , 41 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies focused on addressing follow-up for women with abnormal Pap test results (cytology) and two focused on women who had abnormal HPV testing results [ 37 , 40 ]. Two did not specify the type of abnormal result [ 26 , 33 ] and one focused on abnormal VIA results [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies focused on participant perceptions. Patients from underserved populations with unmet basic needs reported highly valuing their patient navigator during initial appointments because they provided key information, were person‐centered, and brought comfort to patients 127–129 . Commonly reported unmet needs included housing, financial, legal, and transportation issues 130 .…”
Section: Resultsmentioning
confidence: 99%
“…Patients from underserved populations with unmet basic needs reported highly valuing their patient navigator during initial appointments because they provided key information, were person-centered, and brought comfort to patients. [127][128][129] Commonly reported unmet needs included housing, financial, legal, and transportation issues. 130 Participants highlighted the need for patient navigation to address institutional barriers by setting recruitment goals for minority participation in clinical trials and ensuring that interventions are accessible to minorities and that community outreach is used to build awareness.…”
Section: Perceptions Of Patients and Providersmentioning
confidence: 99%
“…Community outreach is necessary to inform uninsured women about the existence of preventative medical screenings and to link them to affordable care. Prior studies have shown that patient navigation can increase screening uptake [42][43][44]. Helping patients move through the complex healthcare system might make the process less daunting.…”
Section: Plos Onementioning
confidence: 99%